The Current State of Transnational Organized Crime - Golubovskii, Vladimir; Kostyuk, Mikhail; Kunts, Elena (International Journal of Criminology and Sociology, 2022)
The paper indicates that criminal groups may differ in terms of size, the scope of operations, types of activities, territorial range, relations with authorities and management, internal organization, and the set of means and methods used to promote their criminal activities and to guard against measures taken by the Government and law enforcement bodies. When national, historical, and cultural differences are taken into account, the diversity of criminal organizations becomes even more evident, while prevention and suppression pose even greater challenges for law enforcement agencies, especially in countries where these organizations are active in their illegal activities. The study is aimed at analyzing national-level legislative measures that may be efficient about one type of organized criminal group, but may not be appropriate for other types. To solve the problems formulated, a complex methodology will be required, combining empirical studies of specific facts and a fundamental theoretical understanding of the conceptual foundations of the problem posed. The results of the analysis made it possible to theoretically substantiate the increased social danger of transnational organized criminal groups, which entails the adoption of appropriate legislative measures. Identifying the latency level of transnational crimes will make it possible to assess the efficiency of the existing sets of measures against it, as well as to formulate recommendations on improving the system of legislative measures to prevent the activities of transnational criminal organizations. A gap in the study can be attributed to the insufficient amount of statistical information on the analyzed crime. The novelty of the research lies in the comprehensive analysis of the current state of transnational organized crime.